An Integrated Financial–Operational Framework for Capital Equipment Decisions: Advancing Manufacturing Investment Theory and Practice - Saad, Hamza (Asia Pacific Economic and Management Review, 2026)
The study combines both operational and financial perspectives of capital investment decisions in the manufacturing field, comparing a manufacturer’s choice of acquiring a new laser cutting machine against continuing to use their current machinery. The study was conducted over a 6-month period in 2025, where two types of finance were analyzed: a single payment of 700,000 as opposed to two payments of 500,000 at the end of Year 1 and Year 2. A discounted cash flow analysis was completed for both types of finance with discount rates (5% - 12%) to measure the financial efficiency of both finance types, while the operational analysis analyzed all costs associated with labor, energy, maintenance and capital costs in order to determine the cost per unit produced. Upfront payment method was the most financially efficient option. At an 8% discount rate, the combined present value of the two installments (891,632) was 191,632 greater than the upfront cost with 27.4%. The operational analysis concluded that the new laser cutting machine had a significantly greater uptime (95%) compared to the legacy machine’s (60%) uptime and had much lower scrap (2%) compared to the legacy machine’s (5%). However, the total cost per unit produced by the new laser cutting machine (13.16) was almost double that of the legacy machine (6.74). The developed integrated framework is transferable across all industries and therefore can be used by manufacturers of all types and sizes to align strategic financial feasibility with operational efficiency when making investment decisions.